Support Vector Machine Outperforms Other Machine Learning Models in Early Diagnosis of Dengue Using Routine Clinical Data - Ariba Qaiser; Sobia Manzoor; Asraf Hussain Hashmi; Hasnain Javed; Anam Zafar; Javed Ashraf (Advances in Virology)
Conclusion: Our study documents three circulating serotypes in the capital territory of Pakistan and highlights that the SVM outperformed other models, potentially serving as a valuable tool in clinical settings to aid in the rapid diagnosis of DF.